Locoregional Lymph Node Recurrence of Trunk Melanoma in Non-sentinel Lymph Node Basins: An Observational Retrospective Study - Ruggero Moro; Jessica González-Ramos; Silvestre Martínez-García; Celia Requena; Victor Traves; Esperanza Manrique-Silva; Eduardo Nagore (Medical Journals Sweden, 2020)
Locoregional lymph node recurrences of primary trunk melanoma can occur in basins not identified during sentinel lymph node biopsy. However, the factors associated with recurrences in non-sentinel lymph node basins are unknown. To evaluate these factors, this observational retrospective study examined the patterns of first lymph node recurrence and the factors associated with recurrence in non-sentinel lymph node basins. A total of 305 patients with primary trunk melanoma who had undergone sentinel lymph node biopsy from 2000 to 2015 were evaluated. Twenty-three patients presented locoregional lymph node recurrence; 8 of which (34.8%) were in non-sentinel lymph node basins. Non-sentinel lymph node recurrences were more frequent in patients with positive sentinel lymph nodes and in those patients whose number of tumour-involved nodes was > 3. These results suggest that clinical examination and ultrasound surveillance should be performed on all potential lymph node drainage basins of trunk melanomas.